A Systematic Review of Pica and Geophagy in Japan and Korea - Golden, Christopher D.; Ahn, Curie; Okubo, Yusuke; Suzuki, Satowa; Yi, Young S. (Asian Journal of Interdisciplinary Research, 2019)
Pica, the craved and purposive consumption of non-food substances, is a globally widespread behavior that has critical connections to public health. Although there is a rich literature describing these behaviors from nearly every culture around the world, there is a dearth of English language literature reporting these behaviors in Japan and Korea. Here, we systematically reviewed the medical evidence of pica in Korean and Japanese language journals to confirm their presence in these cultures and to characterize culturally-specific factors associated with these behaviors. We used Ichusi-Web and KoreaMed with a broad variety of recombined search terms including “pica,” “geophagy,” “amylophagy,” and “trichobezoar” in Korean and Japanese characters. Our results confirm that pica is present in both of these cultures, with particularly frequent reports of trichobezoar (the consumption of human hair).